The role of the madura cattle-field crops integration system model in increasing farmers' income - Hopid, Hopid; Santosa, Ribut; Rahman, Sindi Arista; Hamzah, Amir; Jasuli, Darma (AGROMIX, 2026)
Introduction: The integration between cattle farming and agricultural crops has long been known as a strategy to improve efficiency in the use of natural resources. The cattle-crop integration system model enables synergy between these two sectors and plays a significant role in increasing farmer income in Madura. This research aims to analyze the role of the Madura cattle-field crop integration model in increasing farmer income. Methods: Samples were selected using purposive sampling technique, with criteria for farmers who have implemented the integration system for at least five years. The sample size was determined based on the availability of data that could be obtained and statistical analysis needs. The analysis method used Structural Equation Modeling-Partial Least Square (SEM-PLS). This design was chosen because SEM-PLS can handle latent variables and test relationships between variables simultaneously. Results: The analysis results show that both cattle maintenance and field crop management contribute significantly to increasing farmer income, with path coefficient values of 0.392 and 0.502 respectively, and T-statistic values > 1.96 (p-value < 0.05). Conclusion: An R² value of 0.370 indicates that about 37% of farmers' income variations are explained by this integrated system, while the rest is influenced by external factors outside the model, this result is strong enough to illustrate the strategic role of the integration model in sustainable agribusiness systems.